HISTORY AND RESULTS OF HYDROACOUSTIC RESEARCHES IN THE NORTH CASPIAN - G. M. Abdurakhmanov; L. A. Zykov; A. F. Sokolsky; N. N. Popov; G. A. Kuanysheva; E. A. Sokolskaya (Юг России: экология, развитие, 2016)
Aim. We present materials on the history of hydroacoustic research in the Caspian Sea and forecast of catches in case of abolition of the law prohibiting the fishing in the open sea.Methods. We have carried out three hydroacoustic surveys in accordance with existing procedures. Investigations have been conducted using fish-finding multifunctional sonar panorama video-plotter.Results. Hydroacoustic researches on the density of accumulations, spatial distribution and stocks of Caspian Sea migrating herring (Dolginskaya herring, Caspian and bigeye shads) were carried out in the period of April - May 2007, in the shallow part of the North Caspian Sea, and for this we have performed two hydroacoustic surveys. In the spring, in different areas of surveyed area size and weight characteristics of marine migratory herrings were fairly stable; the length of Dolginskiy herring caught in control fixed nets in different parts of the area surveyed ranged from 23.6 cm. to 30.0 cm, with an average of 26,7 cm; as for the weight, it fluctuated from 212.3g. to 393g, with an average of 275.0 g. These data indicate that the temperature factor is one of the most important abiotic factors that determine the density of accumulations, places and areas of migratory sea herring in the pre-spawning period.Conclusion. Using hydroacoustic sonar method in the Caspian Sea for more than 40 years has shown its representativeness and reliability in assessing marine fish stocks. The number of marine migratory herring in the North Caspian Sea is closely linked to the temperature of the water and with the increase in temperature we can observe increase in the number. The biomass of marine migratory herrings in the Northern Caspian Sea varies from 3 to 5 thousand tons, which is a significant reserve for the fishing industry of Kazakhstan and Russia. Under the current economic conditions the hydroacoustic sonar method is to become a major tool for assessment of fish stocks in the North Caspian.